Maximum local thermal effects carpet plot for symmetric lamited composite plates - Beng, Ahmad Hong Kueh (Trans Tech Publications, 2011)
Maximum local thermal effects carpet plots for symmetric laminated composite plates used in the design and optimization for material under heat loads are produced and demonstrated. The independent variables considered in this paper are the proportions of 0, 45, and 90 degrees ply orientations in the laminates. The carpet plots are presented in such a way that when the failure stress or strain of a composite lamina is known, all possible safe ply orientation proportion can be determined. In addition, the dependency of the carpet plots in correspondence to the temperature change is investigated. It is found that the shapes of both thermal stress and strain plots are practically identical.